The Role of Informants and Archive Films in the Hungarian Folk Dance Revival Movement - Anna Janku (Muzikološki Zbornik)
The Hungarian táncház [dance house] movement revolutionised the revival of traditional folk dances in urban contexts. This study examines the role of adatközlők [informants], master–disciple relationships, and archival film recordings as reference sources in the transmission and reconstruction of traditional dances within the Hungarian folk dance revival.